Impaired olfactory discrimination learning and decreased olfactory sensitivity in aged C57Bl/6 mice - Patel, Roseanne C. (2007)
Young (4 months) and old (24 months) C57Bl/6J mice were tested in an automated simultaneous-cue, two-odor discrimination task. The mice were first pre-trained to execute trial-structured nose poke responses in a straight alley. They were then trained to criterion on a series of eight novel olfactory discrimination problems. Old mice required slightly more shaping sessions to acquire the nose poke response. The old mice required many more sessions and made seventy percent more errors than young mice before reaching criterion performance on the series of eight olfactory discrimination problems. Young and old mice did not differ in retention of the last odor discrimination when tested two weeks after training. Old mice had significantly higher thresholds for discriminating ethyl acetate vapor from non-odorized air. The results suggest that mice may be a good model for study of olfactory dysfunction and cognitive deficits with aging.